НАЦІОНАЛЬНО-ПАТРІОТИЧНЕ ВИХОВАННЯ ПОЛІЦЕЙСЬКИХ ЯК НЕВІД’ЄМНА СКЛАДОВА ЗАБЕЗПЕЧЕННЯ ВНУТРІШНЬОЇ БЕЗПЕКИ УКРАЇНИ - Загуменна, Юлія Олександрівна (SUPREMANCE OF LAW, 2017)
The article analyzes the role and the place of national and patriotic education of police officers in the system of ensuring the internal security of Ukraine. Have been examined the peculiarities of national, patriotic and ethical education of future police officers. In the article has been analyzed the effectiveness of the legislation of Ukraine concerning the organization and conduct of national and patriotic education, proposals on increasing the efficiency of state policy in this area have been developed.